Histogram Peak Normalization Based Threshold to Detect Brain Tumor from T1 Weighted MRI - Sarkar, Kanishka; Mandal, Ardhendu; Mandal, Rakesh Kumar (International Journal of Computer Sciences and Engineering, 2025)
Medical imaging is a process of creating images of interior body organs or parts which is very useful for diagnose, clinical analysis and treatment of specific disease. Magnetic Resonance Imaging (MRI) is amedical imaging technique used primarily in medical settings to produce high quality images of the inside of the human body or parts. MRI has become effective way to study brain tumors.Threshold based image segmentation is a common technique often used to detect the tumor object. The literature survey depicts that most of the existing methods have ignored the poor quality images. In this paper a method has been proposed based on histogram segmentation to detect the brain tumor from T1 weighted MRI images. T1 weighted MRI images of brain has been takenas input. This system includes image filtering, image segmentation, and object extraction for the purpose. The whole procedure has been implemented in MATLAB.